THE ANALYSIS OF TEMPORAL DEIXIS TERMS IN THE SONG LYRICS OF “THAT’S THE SPIRIT ALBUM BY BRING ME THE HORIZON - Swastana, I Wayan Bayu; Maharani, Putu Devi; Nugraha, I GB Wahyu (Institut Pariwisata dan Bisnis Internasional, 2021)
This study is focused on the temporal deixis of “That’s the Spirit” album by Bring Me the Horizon. In a language an expression that used for pointing person, location, and time is called deixis. Deixis is part of pragmatics that concern with context in language. There are two objectives in this study which are (1) to find out the temporal deixis terms in “That’s the Spirit” album (2) to analyze the context of temporal deixis in “That’s the Spirit” album. The data collection in this study is done by using documentation method and qualitative method is used for explaining the result of the data. The temporal deixis is divided into three terms which are specific time, pure deictic term, and the last is verb tense, those classification has three roles in the language which are for pointing the time of utterance is happened before the utterance or in the past, at the moment or the action happened at the same time with the utterance and the last is the action happened after the utterance or in the future. The result of this has found verb tense with 87.20% of 75 data, then the pure deictic word with 11.63% of 10 data and the last is 1.17% of specific time with 1 data only.